2019
DOI: 10.1007/s12253-019-00652-x
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Lipoxygenases as Therapeutic Targets in Malignant Pleural Mesothelioma

Abstract: Advanced malignant pleural mesothelioma (MPM) has an extremely poor prognosis with limited chemotherapy options, therefore the identification of new therapeutic targets would aid in disease management. Arachidonic acid is metabolised by cyclooxygenase and lipoxygenase enzymes. The lipoxygenase isoenzymes 5-LOX and 12-LOX have been implicated in carcinogenesis. We aimed to examine 5-LOX and 12-LOX protein expression in a large retrospective series of mesothelioma samples. Further to this, the in vitro cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Inhibition with baicalein was effective in all three cell lines at low concentrations with IC 50 between 9.6µM and 20.7µM respectively. Thus, baicalein holds promise in therapy for malignant pleural mesothelioma [233]. Similar studies have demonstrated the use of both ALOX12 and ALOX5 inhibitors in pancreatic cancer cells PANC-1 and Capan2, which were shown to express ALOX5 and ALOX12.…”
Section: Inhibitors Of Alox In Anti-cancer Therapiesmentioning
confidence: 61%
“…Inhibition with baicalein was effective in all three cell lines at low concentrations with IC 50 between 9.6µM and 20.7µM respectively. Thus, baicalein holds promise in therapy for malignant pleural mesothelioma [233]. Similar studies have demonstrated the use of both ALOX12 and ALOX5 inhibitors in pancreatic cancer cells PANC-1 and Capan2, which were shown to express ALOX5 and ALOX12.…”
Section: Inhibitors Of Alox In Anti-cancer Therapiesmentioning
confidence: 61%